2011
DOI: 10.2196/jmir.1867
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of Cloud Computing to Improve Health Care Services

Abstract: Cloud computing is a new way of delivering computing resources and services. Many managers and experts believe that it can improve health care services, benefit health care research, and change the face of health information technology. However, as with any innovation, cloud computing should be rigorously evaluated before its widespread adoption. This paper discusses the concept and its current place in health care, and uses 4 aspects (management, technology, security, and legal) to evaluate the opportunities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
229
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(248 citation statements)
references
References 51 publications
1
229
0
4
Order By: Relevance
“…Kuo in [4] recommended four aspects to be assessed when adopting health Cloud Computing: management, technology, security, and legal. Kuo also proposed a Healthcare Cloud Computing Strategic Planning (HC2SP) model.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Kuo in [4] recommended four aspects to be assessed when adopting health Cloud Computing: management, technology, security, and legal. Kuo also proposed a Healthcare Cloud Computing Strategic Planning (HC2SP) model.…”
Section: Related Workmentioning
confidence: 99%
“…Cloud Computing is a developing phenomenon in the ICT field that has gained increasing attention from healthcare organisations to overcome some of the e-health barriers [4]. Although there is no generally accepted definition of Cloud Computing [4,5], most of the definitions emphasise similar aspects [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, according to Table 1, it can be demonstrated that in order to explain the adoption of several diverse IS innovations; TOE framework can successfully be utilized. Likewise, the TOE model was applied and tested in Asian, European, and American, in addition to both developed and developing countries [73], [83][84][85]. To all intents and purposes, the experts generally agree on the three TOE dimensions suggested by Tornatzky and Fleischer [76], including the effect of environment, organization and technology adoption.…”
Section: Technology-organization-environment Frameworkmentioning
confidence: 99%
“…In this respect, a study [9] suggests that a high-level integration of data, interoperability, and its sharing are essential among different healthcare practitioners and institutions to deliver secured high-quality healthcare to the patients they serve. In 2011, Kuo reported that cloud computing (a form of distributed computing) is a developing phenomenon in the field, Information Communication Technology (ICT) field that has gained increasing attention from healthcare organisations to overcome some of the e-health barriers [10]. He claimed that ICT can offer economic savings by decreasing the initial and operational costs of e-health to a great extent.…”
Section: Introductionmentioning
confidence: 99%